A structure and function integrated magnesium alloy based on cold metal transfer arc additive manufacturing and a preparation method thereof

CN122895649APending Publication Date: 2026-10-13JIANGSU FURUI NEW MATERIALS TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611379454.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0012]针对现有技术无法实现镁合金构件结构承载与电磁屏蔽原生一体化的不足,本发明的目的在于提供一种基于冷金属过渡电弧增材制备的结构功能一体化镁合金及其制备方法

Benefits of technology

[0024]1、显著提升电磁屏蔽性能与稳定性,解决传统铸造镁合金组织缺陷多、屏蔽性能波动大的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122895649A_ABST
    Figure CN122895649A_ABST
Patent Text Reader

Abstract

The application discloses a kind of structural function integration magnesium alloy based on cold metal transition electric arc additive preparation and preparation method thereof, it is related to metal additive manufacturing technical field, and its technical scheme main point is: step one: the forming substrate is pretreated;Step two: using cold metal transition electric arc additive process, magnesium alloy wire is deposited on the forming substrate according to preset path layer by layer stacking, the parameters of the cold metal transition electric arc additive process include: wire feeding speed 6.4~9.5 m / min, welding speed 9~10.5 m / min, layer height 2.5~2.7 mm, interlayer temperature 15~21 ℃;Effect is using the process characteristics of CMT low heat input, rapid solidification, preparation obtains uniform fine equiaxial crystal organization and dispersed distribution second phase, and layered periodic microstructure formed by layer-by-layer deposition can produce multiple reflection-absorption synergistic enhancement effect on electromagnetic wave, and the prepared AZ31 magnesium alloy component is significantly better than conventional cast magnesium alloy of same composition, and the stability and wideband adaptability of shielding performance are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal additive manufacturing technology, and more specifically, to a method for preparing magnesium alloy components with high electromagnetic shielding performance based on cold metal transition (CMT) arc additive manufacturing. Background Technology

[0002] With the rapid development of 5G communication, radar detection, aerospace electronic equipment, and new energy vehicle electronic control systems, electromagnetic radiation pollution has become an increasingly prominent issue. Electromagnetic interference (EMI) not only affects the normal operation of electronic equipment, reduces its reliability and lifespan, but may also pose potential hazards to human health. Therefore, developing structural-functional integrated materials that combine lightweight design, structural load-bearing capacity, and excellent electromagnetic shielding performance has become an important research direction in the field of materials science and engineering.

[0003] Magnesium alloys, currently the lightest metallic structural materials used in engineering applications, have a density of only 1.74 g / cm³. They also possess a combination of advantages, including high specific strength, high specific stiffness, good damping and vibration reduction performance, and excellent electromagnetic shielding properties, earning them the reputation of "green engineering materials for the 21st century." Existing research indicates that, for the same thickness, magnesium alloys generally outperform aluminum alloys in electromagnetic shielding performance, exhibiting a significant lightweight advantage and promising broad application prospects in aerospace, rail transportation, new energy vehicles, and communication equipment.

[0004] However, the fabrication of traditional magnesium alloy components mainly relies on processes such as casting, rolling, and extrusion. Casting is prone to metallurgical defects such as coarse dendrites, shrinkage cavities, porosity, and compositional segregation, resulting in discontinuous electron transport channels, large fluctuations in conductivity, and poor stability of electromagnetic shielding performance, making it difficult to meet the requirements of high-end equipment for wide-band and high-stability shielding performance. Although plastic deformation processes such as rolling and extrusion can refine grains and improve conductivity, they are difficult to use to fabricate structural components with complex internal cavities, thin walls, or irregular cross-sections, and there are limitations in texture control, which seriously restricts the widespread application of magnesium alloys in the field of integrated electromagnetic shielding functional and structural components.

[0005] Currently, the main technical approaches to improving the electromagnetic shielding performance of magnesium alloys include:

[0006] (1) Alloy composition optimization: The microstructure and electrical conductivity of magnesium alloys can be controlled by adding rare earth elements (such as Y, Nd, Gd, Ce, etc.) or transition elements (such as Zn, Mn, etc.). For example, adding Y to Mg-Zn-Zr alloys can generate Mg3Zn6Y (I phase) and Mg3Zn3Y2 (W phase) second phases, while refining the matrix grains and significantly improving the material's electrical conductivity and shielding performance; the electromagnetic shielding effectiveness of Mg-Zn-Zr alloys containing 2wt.%Y can reach 79-118dB. However, this type of method is still based on the casting and forging process route and cannot fundamentally solve the problem of forming complex components.

[0007] (2) Plastic Deformation and Heat Treatment: The grain size, texture, and second phase distribution of magnesium alloys are controlled by plastic deformation such as rolling and extrusion, followed by heat treatment. For example, after peak aging treatment, the shielding effectiveness of extruded ZK60 magnesium alloy can reach 72dB at a frequency of 1200MHz, which is 16dB higher than that of unaged extruded alloy; the shielding effectiveness of rolled AZ31 magnesium alloy can reach 63-82dB under 57% reduction. However, this type of process is only suitable for simple structural blanks and cannot meet the needs of preparing complex structural components.

[0008] (3) Composite materials and coating technology: The electromagnetic shielding performance of magnesium alloys can be improved by adding reinforcing phases such as carbon nanotubes and nano-iron particles or by preparing composite coatings. However, this type of technology is complex, has high preparation costs, and has problems such as poor interfacial compatibility, easy wear and peeling of coatings, and increased overall weight of components, resulting in insufficient reliability in long-term service.

[0009] Arc additive manufacturing technology relies on the "discrete-stacking" forming principle, which can directly form complex components based on a three-dimensional model. It has advantages such as no need for molds, high material utilization, and low manufacturing cost. Among them, the cold metal transition arc additive manufacturing process has the characteristics of low heat input, high forming stability, and minimal spatter, and is particularly suitable for the efficient forming of magnesium alloy materials with high chemical reactivity and easy oxidation.

[0010] In recent years, a few studies have begun to explore the application of additive manufacturing technology in the field of magnesium alloy electromagnetic shielding. For example, although magnesium alloys prepared using selective laser melting (SLM) technology can achieve a fine-grained structure, they are limited by safety risks such as the flammability and explosiveness of magnesium powder, as well as insufficient component density and limited forming size, making it difficult to achieve low-cost preparation of large-size complex components. Furthermore, existing WAAM processes mostly use single-wire deposition throughout the entire process, resulting in uniform material properties. This makes it difficult to design differentiated performance according to the service requirements of different areas of the component, and thus fails to achieve integrated coupling of structural load-bearing and electromagnetic shielding functions.

[0011] In summary, current research on the electromagnetic shielding performance of magnesium alloys is still mainly focused on traditional cast and wrought magnesium alloys. Systematic research on the electromagnetic shielding performance of magnesium alloy components manufactured by CMT arc additive manufacturing is relatively scarce. The intrinsic relationship between CMT process parameters, microstructure, and electromagnetic shielding performance has not yet been established, nor has a composition-process synergistic optimization scheme that can take into account both mechanical properties and electromagnetic shielding performance been proposed. As a result, it is impossible to meet the application requirements of high-end equipment for integrated structural and functional magnesium alloy components. Summary of the Invention

[0012] To address the shortcomings of existing technologies in achieving native integration of structural load-bearing and electromagnetic shielding in magnesium alloy components, this invention aims to provide a structurally and functionally integrated magnesium alloy and its preparation method based on cold metal transition arc additive manufacturing. Using CMT (Continuous Metal Transition) technology as the core, and through synergistic control of process, microstructure, and properties, the dual functions of mechanical load-bearing and broadband electromagnetic shielding are achieved in situ on the same magnesium alloy matrix, without the need for additional plastic deformation or functional coatings. Furthermore, gradient functional integration design can be achieved through layered deposition of dissimilar materials, adapting to the complex service requirements of high-end equipment.

[0013] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a magnesium alloy component with high electromagnetic shielding performance based on cold metal transition arc additive manufacturing, comprising the following steps:

[0014] Step 1: Pre-treat the substrate;

[0015] Step 2: Using a cold metal transition arc additive manufacturing process, magnesium alloy wires are stacked and deposited layer by layer on the formed substrate according to a preset path. The parameters of the cold metal transition arc additive manufacturing process include: wire feed speed 6.4~9.5m / min, welding speed 9~10.5m / min, layer height 2.5~2.7mm, and interlayer temperature 15~21℃.

[0016] By synergistically controlling the above process parameters, and relying on the characteristics of low heat input and rapid solidification of the cold metal transition process, fine equiaxed crystal structure and diffusely distributed second phase are obtained to ensure the mechanical properties of the structure. At the same time, by using the naturally formed layered periodic microstructure deposited layer by layer, a multi-reflection-absorption synergistic attenuation channel for electromagnetic waves is constructed to improve the broadband electromagnetic shielding performance. The functions of structural load-bearing and electromagnetic shielding are integrated in situ in the magnesium alloy matrix.

[0017] Furthermore, the magnesium alloy wire is AZ31 magnesium alloy wire, and its chemical composition by mass percentage is: Al 2.5%~3.5%, Zn 0.7%~1.3%, Mn 0.1%~0.5%, with the balance being Mg; the parameters of the cold metal transition arc additive manufacturing process are: wire feed speed 6.5~9.5m / min, welding speed 9~10.5m / min, layer height 2.5~2.7mm, arc ignition current coefficient 0.85~1.1, and arc length correction coefficient -1~5.

[0018] Furthermore, the magnesium alloy wire is WE43 magnesium alloy wire, and its chemical composition by mass percentage is: Y 3.7%~4.3%, Nd 2.4%~4.0%, Zr 0.4%~1.0%, Gd 0.4%~1.5%, with the balance being Mg; the parameters of the cold metal transition arc additive manufacturing process are: wire feed speed 6.4~7.8m / min, welding speed 10.5m / min, layer height 2.5mm, arc ignition current coefficient of 1~1.1, and arc length correction coefficient of 5.

[0019] Furthermore, after deposition, the WE43 magnesium alloy components are subjected to T6 heat treatment, including: solution treatment at 500℃ for 3 hours, followed by artificial aging treatment at 225℃ for 8 hours, and water quenching.

[0020] Further, the magnesium alloy component is an AZ31 / WE43 dissimilar magnesium alloy cold metal transition arc additive fusion component; in step two, AZ31 magnesium alloy wire and WE43 magnesium alloy wire are alternately deposited on the AZ31 magnesium alloy substrate in layers, with 8 passes per layer and a total of 20 layers, and the welding direction is kept consistent; the AZ31 layer deposition adopts the parameters of wire feed speed 6.5-9.5m / min, welding speed 9-10.5m / min, and layer height 2.5-2.7mm, and the WE43 layer deposition adopts the parameters of wire feed speed 6.4-7.8m / min, welding speed 10.5m / min, and layer height 2.5mm, and the interlayer temperature is controlled at 15-21℃.

[0021] Furthermore, the chemical composition of the AZ31 magnesium alloy wire, by mass percentage, is: Al 2.5%–3.5%, Zn 0.7%–1.3%, Mn 0.1%–0.5%, with the balance being Mg; the chemical composition of the WE43 magnesium alloy wire, by mass percentage, is: Y 3.7%–4.3%, Nd 2.4%–4.0%, Zr 0.4%–1.0%, Gd 0.4%–1.5%, with the balance being Mg.

[0022] Another objective of this invention is to provide a high electromagnetic shielding magnesium alloy component, wherein the component has a layered periodic microstructure, the matrix is ​​a fine equiaxed crystal structure, and the second phase is dispersedly distributed; the electromagnetic shielding effectiveness is not less than 82dB in the 30-1500MHz frequency band and not less than 82dB in the 8.2-12.4GHz frequency band.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. Significantly improves electromagnetic shielding performance and stability, solving the problems of numerous microstructural defects and large fluctuations in shielding performance in traditional cast magnesium alloys.

[0025] This invention utilizes the low heat input and rapid solidification characteristics of CMT (Continuous Metallurgical Transformation) to prepare a uniform and fine equiaxed crystal structure and a diffusely distributed second phase. Simultaneously, the layered periodic microstructure formed by layer-by-layer deposition can exert a synergistic enhancement effect of multiple reflections and absorptions on electromagnetic waves. The prepared AZ31 magnesium alloy components have an electrical conductivity of 9.89 MS / m, and an electromagnetic shielding effectiveness of 82–102 dB in the 30–1500 MHz frequency band and 92–101 dB in the 8.2–12.4 GHz frequency band, significantly outperforming conventional cast magnesium alloys of the same composition. The stability and wide-band compatibility of the shielding performance are greatly improved.

[0026] 2. Break through the conductivity bottleneck of rare earth magnesium alloys and solve the inherent defect of rare earth alloys being "high in strength but poor in electromagnetic shielding".

[0027] This invention proposes a CMT fusion scheme for AZ31 / WE43 dissimilar magnesium alloys. By reducing the local rare earth element content through composition dilution, and synergizing with the rapid solidification of CMT, it weakens lattice distortion and electron scattering caused by rare earth elements, thus optimizing electron transport channels. The conductivity of the fused region reaches 9.51 MS / m, approaching the performance level of CMT-AZ31 and significantly exceeding the 6.03 MS / m of CMT-WE43 alone, achieving the dual objectives of "preserving mechanical properties and significantly improving electromagnetic shielding performance" in rare earth magnesium alloys.

[0028] 3. Achieve integrated structural load-bearing and electromagnetic shielding functions, solving the problem that traditional processes cannot simultaneously address complex configurations and comprehensive performance.

[0029] This invention leverages the complex configuration forming capabilities of CMT arc additive manufacturing to directly fabricate irregularly shaped, thin-walled, and cavitary integrated components without subsequent plastic deformation. The AZ31 magnesium alloy deposited component exhibits a horizontal tensile strength of 262.6 MPa, a yield strength of 125 MPa, and an elongation of 23.4%, with mechanical properties approaching those of the extruded state, while also possessing excellent broadband electromagnetic shielding performance. The WE43 magnesium alloy deposited component, after T6 heat treatment, achieves a peak hardness of 93.2 HV, approximately 17% higher than the deposited state, maintaining electromagnetic shielding performance while meeting the requirements for high-temperature and high-load service, truly realizing structural-functional integration.

[0030] 4. Provides flexible material-process matching solutions to address the performance limitations and poor adaptability of single additive manufacturing solutions.

[0031] This invention allows for flexible selection of manufacturing schemes based on different service scenarios: for cost-sensitive applications with high requirements for conductive shielding and room temperature operation, the AZ31 magnesium alloy CMT additive manufacturing scheme can be selected; for applications with high temperature, high load, and high corrosion resistance requirements, the WE43 magnesium alloy CMT additive manufacturing scheme can be selected and supplemented with T6 heat treatment; for applications that require both high strength and high shielding performance, the AZ31 / WE43 dissimilar fusion scheme can be adopted, with a clear process window and strong scenario adaptability.

[0032] 5. Clarify the performance regulation mechanism to provide theoretical and technical support for engineering applications.

[0033] This invention systematically establishes the intrinsic relationship between CMT process parameters, microstructure, and electromagnetic shielding performance, elucidates the mechanism by which fine grain strengthening, second-phase dispersion, and layered periodic structure synergistically enhance electromagnetic shielding performance, and provides a clear technical path for the regulation of electromagnetic shielding performance of magnesium alloy CMT additive components, possessing strong engineering guiding significance. Attached Figure Description

[0034] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings:

[0035] Figure 1 (a) Schematic diagram of the manufacturing process for arc additive manufacturing of AZ31 magnesium alloy thin-walled parts; (b) Macroscopic morphology and metallographic sampling locations;

[0036] Figure 2 This is a process flow diagram of the preparation process of magnesium alloy components manufactured by CMT arc additive manufacturing according to the present invention.

[0037] Figure 3 This is a metallographic structure and grain distribution diagram of the longitudinal section of the CMT-AZ31 magnesium alloy component of the present invention;

[0038] Figure 4 The XRD patterns of the top, middle and bottom of the CMT-AZ31 magnesium alloy sample of this invention are shown.

[0039] Figure 5 This is a microhardness distribution diagram of the longitudinal section of the CMT-AZ31 magnesium alloy sample of the present invention;

[0040] Figure 6 These are stress-strain curves of different regions in the horizontal direction of the CMT-AZ31 magnesium alloy of this invention.

[0041] Figure 7The electromagnetic shielding effectiveness curve of the CMT-AZ31 magnesium alloy of the present invention is shown in the figure, where (a) is the frequency band of 30MHz to 1500MHz and (b) is the frequency band of 8.2 to 12.4GHz.

[0042] Figure 8 These are X-ray diffraction patterns of different regions of the CMT-WE43 magnesium alloy of this invention;

[0043] Figure 9 This is a metallographic structure and grain distribution diagram of the longitudinal section of the CMT-WE43 magnesium alloy component of the present invention;

[0044] Figure 10 This is a microhardness distribution diagram of the CMT-WE43 magnesium alloy sample of this invention;

[0045] Figure 11 These are stress-strain curves of different regions in the horizontal direction of the CMT-WE43 magnesium alloy of this invention;

[0046] Figure 12 The electromagnetic shielding effectiveness curve of the CMT-WE43 magnesium alloy of the present invention is shown in the figure, where (a) is the frequency band of 30MHz to 1500MHz and (b) is the frequency band of 8.2 to 12.4GHz.

[0047] Figure 13 This is a metallographic diagram of the fusion region of CMTAZ31 and WE43 in this invention;

[0048] Figure 14 This is a hardness distribution diagram of the fusion region of CMTAZ31 and WE43 in this invention;

[0049] Figure 15 The images show the microstructure and EDS analysis of the transition region between WE43 and AZ31 in the CMT magnesium alloy of this invention, where (a) is the BSE morphology and EDS surface scan, and (b) is the line scan image.

[0050] Figure 16 This is a graph showing the electromagnetic shielding performance of the WE43 / AZ31 magnesium alloy dissimilar fusion component of the present invention. Detailed Implementation

[0051] The performance of three types of integrated structural and functional magnesium alloy components is verified through three examples: Example 1 is a homogeneous AZ31 integrated component, suitable for room temperature high shielding-medium load conditions; Example 2 is a homogeneous WE43 integrated component, suitable for high temperature high load-medium shielding conditions; Example 3 is an AZ31 / WE43 gradient integrated component, accommodating both high strength and high shielding composite conditions. All examples achieve structural and functional integration in situ through CMT (cold metal transfer) process, without the need for additional functional coatings or plastic deformation treatment.

[0052] All performance tests in the following examples and comparative examples were performed under the same benchmark and conditions to ensure data comparability:

[0053] (1) Microscopic tissue observation: longitudinal section tissue characterization was performed using optical microscope (OM), scanning electron microscope (SEM) and electron backscatter diffractometer (EBSD);

[0054] (2) Phase analysis: Phase identification was performed using an X-ray diffractometer (XRD), with a scanning range of 10° to 90°;

[0055] (3) Mechanical properties: The room temperature tensile test was performed in accordance with GB / T228.1-2010. The specimen was cut in the horizontal direction and the tensile rate was 2 mm / min. The microhardness test was performed with a load of 100 g and a holding pressure of 15 s.

[0056] (4) Electromagnetic shielding performance: The flange coaxial method was adopted, and the test was performed in accordance with GB / T30141-2013 standard. The sample thickness was 2mm, and the test frequency bands were 30MHz~1500MHz and 8.2~12.4GHz.

[0057] Example 1: Fabrication of AZ31 magnesium alloy components by CMT arc additive manufacturing

[0058] This embodiment provides a method for preparing AZ31 magnesium alloy components with high electromagnetic shielding performance based on cold metal transition arc additive manufacturing.

[0059] 1. Material preparation

[0060] AZ31 magnesium alloy wire (1.20 mm in diameter) was selected as the additive manufacturing material. Its chemical composition by mass percentage is: Al 3.17%, Zn 0.96%, Mn 0.35%, with the balance being Mg. AZ31 magnesium alloy sheet was selected as the forming substrate.

[0061] 2. Substrate pretreatment

[0062] The substrate surface is mechanically polished using a bowl brush grinder to remove the surface oxide layer and expose a uniform metallic luster. Then, the substrate surface is cleaned with water and anhydrous ethanol in sequence to remove residual dust and oil. After cleaning, the substrate is dried and firmly clamped onto the worktable of the CMT arc additive manufacturing equipment.

[0063] 3. CMT Arc Additive Deposition

[0064] like Figure 1 As shown, an Arcman S1 welding machine and a Ra5000 welding torch were used, with pure argon as the shielding gas at a flow rate of 20 L / min. The CMT process parameters are shown in Table 1.

[0065] Table 1. AZ31 Magnesium Alloy CMT Arc Additive Manufacturing Process Parameters

[0066] 1st floor 9.5 -1 9 2.7 21 0.85 1.2 0.2 17% 2nd floor 8 -1 9 2.7 21 0.85 1.2 0.2 17% 3 floors 7 -1 9 2.7 21 0.85 1.2 0.2 17% 4 floors 6.5 -1 9 2.7 21 0.85 1.2 0.2 17%

[0067] Single-pass thin-walled components are fabricated by stacking and depositing layers according to a preset path. The overall process flow is as follows: Figure 2 As shown.

[0068] 4. Experimental Results

[0069] (1) Microstructure: such as Figure 3 As shown, the sedimentary structure is dominated by equiaxed crystals, mainly composed of α-Mg matrix and β-Mg... 17 Al 12 It consists of phases and η-Al8Mn5 phase. The grain size increases from 19.9 μm at the bottom to 26.7 μm at the top.

[0070] (2) Phase analysis: such as Figure 4 As shown, the XRD pattern reveals that α-Mg is the dominant phase in all regions of the sedimentary structure, while β-Mg is also present. 17 Al 12 Characteristic diffraction peaks of the phase.

[0071] (3) Mechanical properties: such as Figure 5 As shown, the microhardness exhibits a gradient distribution from bottom to top. Figure 6 As shown, the horizontal tensile strength is 262.6 MPa, the yield strength is 125 MPa, and the elongation is 23.4%.

[0072] (4) Electromagnetic shielding performance: such as Figure 7 As shown, the conductivity is 9.89 MS / m, and the electromagnetic shielding effectiveness is 82–102 dB in the 30–1500 MHz frequency band and 92–101 dB in the 8.2–12.4 GHz frequency band.

[0073] Example 2: Fabrication of WE43 magnesium alloy components using CMT arc additive manufacturing

[0074] This embodiment provides a method for preparing WE43 magnesium alloy components with high electromagnetic shielding performance based on cold metal transition arc additive manufacturing.

[0075] 1. Material preparation

[0076] WE43 magnesium alloy wire (1.20 mm in diameter) was selected as the additive manufacturing material. Its chemical composition by mass percentage is: Y 4.11%, Nd 2.43%, Zr 0.75%, Gd 1.462%, Mn 0.03%, with the balance being Mg. AZ31 magnesium alloy sheet was selected as the forming substrate.

[0077] 2. Substrate pretreatment

[0078] The substrate pretreatment method is the same as in Example 1.

[0079] 3. CMT Arc Additive Deposition

[0080] An Arcman S1 welding machine and a Ra5000 welding torch were used, with pure argon as the shielding gas at a flow rate of 20 L / min. The CMT process parameters are shown in Table 2.

[0081] Table 2. WE43 Magnesium Alloy CMT Arc Additive Manufacturing Process Parameters

[0082] 1st floor 7.8 5 10.5 2.5 15 1 2 0.2 17% 2nd floor 7.6 5 10.5 2.5 15 1 2 0.2 17% 3rd to 4th floors 7.2 5 10.5 2.5 15 1 2 0.2 17% 5 floors 6.8 5 10.5 2.5 15 1.1 2 0.2 17% 6 floors 6.4 5 10.5 2.5 15 1.1 2 0.2 17%

[0083] Single-pass thin-walled components are fabricated by stacking and depositing layers according to a preset path.

[0084] 4. Heat treatment

[0085] To further improve the mechanical properties, the deposited components were subjected to T6 heat treatment: solution treatment at 500℃ for 3 hours, followed by artificial aging treatment at 225℃ for 8 hours, and water quenching.

[0086] 5. Experimental Results

[0087] (1) Phase analysis: such as Figure 8 As shown, the deposited WE43 magnesium alloy is mainly composed of α-Mg phase and a small amount of second phase.

[0088] (2) Microstructure: such as Figure 9 As shown, the sedimentary microstructure is equiaxed with grains ranging from 8.7 to 10.2 μm in size, and the grain boundaries are composed of a network of Mg. 12 Nd phase.

[0089] (3) Mechanical properties: such as Figure 10 As shown, the microhardness of the deposited state is approximately 79.3 HV. After T6 heat treatment, the peak hardness is 93.2 HV, an increase of approximately 17% compared to the deposited state. Figure 11 As shown, the horizontal tensile strength of the sedimentary state is 240.1 MPa, the yield strength is 164 MPa, and the elongation is 11.5%.

[0090] (4) Electromagnetic shielding performance: such as Figure 12 As shown, the conductivity is 6.03 MS / m. The electromagnetic shielding effectiveness is initially 103 dB in the 30–1500 MHz frequency band and remains above 90 dB across the entire frequency band, while it is 82–92 dB in the 8.2–12.4 GHz frequency band.

[0091] Example 3: Preparation of AZ31 / WE43 dissimilar magnesium alloy CMT fused components

[0092] This embodiment provides a method for preparing AZ31 / WE43 dissimilar magnesium alloy CMT fused components.

[0093] 1. Material preparation

[0094] The chemical composition of AZ31 wire is the same as in Example 1, and the chemical composition of WE43 wire is the same as in Example 2. AZ31 magnesium alloy sheet is selected as the forming substrate.

[0095] 2. Substrate pretreatment

[0096] The substrate pretreatment method is the same as in Example 1.

[0097] 3. CMT heterogeneous fusion deposition

[0098] CMT layer deposition was performed on an AZ31 magnesium alloy substrate using alternating AZ31 and WE43 wires. Each layer underwent 8 passes, for a total of 20 layers, with the bonding direction remaining consistent. The AZ31 layer used the process parameters of Example 1, and the WE43 layer used the process parameters of Example 2. The interlayer temperature was controlled between 15 and 21°C.

[0099] 4. Experimental Results

[0100] (1) Interface organization: such as Figure 13 As shown, the interface exhibits wavy fusion lines, free from defects such as cracks and pores, forming a compositional transition zone 40–60 μm wide.

[0101] (2) Component analysis: such as Figure 15 As shown, Al and Zn elements diffuse towards the WE43 side, while Y, Gd, and Zr elements diffuse towards the AZ31 side, with no harmful element segregation. The interface phases are α-Mg and trace amounts of Mg2Y phase, with no brittle Al-Mn or Mg-Al phase.

[0102] (3) Mechanical properties: such as Figure 14 As shown, the hardness smoothly transitions from the WE43 side (80-86 HV) to the AZ31 side (58-72 HV).

[0103] (4) Electromagnetic shielding performance: such as Figure 16 As shown, the conductivity of the fused alloy reaches 9.51 MS / m, which is close to the level of AZ31 (9.89 MS / m) and far exceeds that of the single WE43 (6.03 MS / m), demonstrating excellent broadband shielding capability in the 30-1500MHz frequency band.

[0104] Comparative Example 1: Conventionally Cast AZ31 Magnesium Alloy

[0105] To compare and verify the electromagnetic shielding performance advantages of the CMT arc additive magnesium alloy of this invention, a conventional cast AZ31 magnesium alloy plate (2mm thick) was selected for electromagnetic shielding performance testing.

[0106] Test results show that the electromagnetic shielding effectiveness of conventional cast AZ31 magnesium alloy in the 900MHz and 1500MHz frequency bands is 64dB and 55dB, respectively, while the CMT-AZ31 magnesium alloy prepared in Example 1 of this invention has an effectiveness of approximately 95dB in the 900MHz frequency band and approximately 85dB in the 1500MHz frequency band. The electromagnetic shielding performance of the CMT-AZ31 magnesium alloy of this invention is significantly better than that of conventional cast magnesium alloy of the same composition.

[0107] Comparative Example 2: Commonly Used Alloys in Conventional Casting

[0108] Table 3 lists the electromagnetic shielding performance data of commonly used alloys with a thickness of 2 mm.

[0109] Table 3 Electromagnetic shielding performance of commonly used alloys with a thickness of 2mm

[0110] pure magnesium 51 52 ZK60 55 50 AZ31 64 55 AZ61 59 47 ZM61 49 47 pure copper 36 34 2024 aluminum alloy 35 35

[0111] As shown in Table 3, the electromagnetic shielding performance of the CMT-AZ31 magnesium alloy (approximately 95dB at 900MHz and approximately 85dB at 1500MHz) prepared in Example 1 of this invention is significantly better than all conventional casting alloys in the table, and even better than pure copper and 2024 aluminum alloy.

[0112] The core principle of this invention is as follows: using cold metal transition arc additive manufacturing (CMT) as the forming core, it leverages the low heat input and rapid solidification characteristics of the process to obtain a fine and uniform equiaxed grain structure and a dispersed second phase. The second phase particles can act as heterogeneous nucleation cores to assist in grain refinement and can also generate dispersion strengthening through dislocation pinning, synergistically ensuring the structural mechanical properties of the component with grain refinement strengthening. On the other hand, it utilizes naturally formed layered periodic micro-interfaces through layer-by-layer deposition to construct synergistic attenuation channels for multiple reflections, scattering, and absorption of electromagnetic waves, significantly improving broadband electromagnetic shielding performance. These two types of micro-features are simultaneously formed and in-situ coupled through CMT technology, ultimately achieving the integration of structural load-bearing and electromagnetic shielding functions natively on a magnesium alloy matrix, demonstrating broad industrial application prospects.

[0113] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Those skilled in the art can readily implement the present invention based on the accompanying drawings and the above description. However, any modifications, alterations, or variations made by those skilled in the art without departing from the scope of the present invention, utilizing the disclosed technical content, are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, or variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing magnesium alloy components with high electromagnetic shielding performance based on cold metal transition arc additive manufacturing, characterized in that: Includes the following steps: Step 1: Pre-treat the substrate; Step 2: Using a cold metal transition arc additive manufacturing process, magnesium alloy wires are stacked and deposited layer by layer on the formed substrate according to a preset path. The parameters of the cold metal transition arc additive manufacturing process include: wire feed speed 6.4~9.5m / min, welding speed 9~10.5m / min, layer height 2.5~2.7mm, and interlayer temperature 15~21℃. By synergistically controlling the above process parameters, and relying on the characteristics of low heat input and rapid solidification of the cold metal transition process, fine equiaxed crystal structure and diffusely distributed second phase are obtained to ensure the mechanical properties of the structure. At the same time, by using the naturally formed layered periodic microstructure deposited layer by layer, a multi-reflection-absorption synergistic attenuation channel for electromagnetic waves is constructed to improve the broadband electromagnetic shielding performance. The functions of structural load-bearing and electromagnetic shielding are integrated in situ in the magnesium alloy matrix.

2. The method for preparing a high electromagnetic shielding performance magnesium alloy component based on cold metal transition arc additive manufacturing according to claim 1, characterized in that: The magnesium alloy wire is AZ31 magnesium alloy wire, and its chemical composition by mass percentage is: Al 2.5%~3.5%, Zn 0.7%~1.3%, Mn 0.1%~0.5%, with the balance being Mg; the parameters of the cold metal transition arc additive manufacturing process are: wire feed speed 6.5~9.5m / min, welding speed 9~10.5m / min, layer height 2.5~2.7mm, arc ignition current coefficient 0.85~1.1, and arc length correction coefficient -1~5.

3. The method for preparing a high electromagnetic shielding performance magnesium alloy component based on cold metal transition arc additive manufacturing according to claim 1, characterized in that: The magnesium alloy wire is WE43 magnesium alloy wire, and its chemical composition by mass percentage is: Y 3.7%~4.3%, Nd 2.4%~4.0%, Zr 0.4%~1.0%, Gd 0.4%~1.5%, with the balance being Mg; the parameters of the cold metal transition arc additive manufacturing process are: wire feed speed 6.4~7.8m / min, welding speed 10.5m / min, layer height 2.5mm, arc ignition current coefficient of 1~1.1, and arc length correction coefficient of 5.

4. The method for preparing a high electromagnetic shielding performance magnesium alloy component based on cold metal transition arc additive manufacturing according to claim 3, characterized in that: After deposition, the WE43 magnesium alloy components were subjected to T6 heat treatment, including: solution treatment at 500℃ for 3 hours, followed by artificial aging treatment at 225℃ for 8 hours, and water quenching.

5. The method for preparing a high electromagnetic shielding performance magnesium alloy component based on cold metal transition arc additive manufacturing according to claim 1, characterized in that: The magnesium alloy component is an AZ31 / WE43 dissimilar magnesium alloy cold metal transition arc additive fusion component. In step two, AZ31 magnesium alloy wire and WE43 magnesium alloy wire are alternately deposited on the AZ31 magnesium alloy substrate in layers, with 8 passes per layer and a total of 20 layers, and the welding direction is kept consistent. The AZ31 layer deposition adopts the parameters of wire feed speed of 6.5-9.5m / min, welding speed of 9-10.5m / min, and layer height of 2.5-2.7mm. The WE43 layer deposition adopts the parameters of wire feed speed of 6.4-7.8m / min, welding speed of 10.5m / min, and layer height of 2.5mm. The interlayer temperature is controlled at 15-21℃.

6. The method for preparing a high electromagnetic shielding performance magnesium alloy component based on cold metal transition arc additive manufacturing according to claim 5, characterized in that: The chemical composition of the AZ31 magnesium alloy wire, by mass percentage, is: Al 2.5%–3.5%, Zn 0.7%–1.3%, Mn 0.1%–0.5%, with the balance being Mg; the chemical composition of the WE43 magnesium alloy wire, by mass percentage, is: Y 3.7%–4.3%, Nd 2.4%–4.0%, Zr 0.4%–1.0%, Gd 0.4%–1.5%, with the balance being Mg.

7. The magnesium alloy component prepared by the method according to any one of claims 1 to 6, characterized in that: The component matrix is ​​an equiaxed crystal structure formed by rapid solidification of CMT, with a grain size of 8.7–26.7 μm and a dispersed second phase distribution, providing the structural load-bearing mechanical basis. The component contains a layered periodic microstructure formed by the layer-by-layer deposition of CMT, which can generate multiple reflections and absorptions to enhance electromagnetic waves, providing broadband electromagnetic shielding. The two are coupled in situ to achieve structural and functional integration. The component has an electromagnetic shielding effectiveness of 82–102 dB in the 30–1500 MHz frequency band and 82–101 dB in the 8.2–12.4 GHz frequency band.

8. The magnesium alloy component according to claim 7, characterized in that: When the magnesium alloy component is an AZ31 magnesium alloy component prepared by the method described in claim 2, its electrical conductivity is 9.89 MS / m, its tensile strength in the horizontal direction is 262.6 MPa, its yield strength is 125 MPa, and its elongation is 23.4%.

9. The magnesium alloy component according to claim 7, characterized in that: When the magnesium alloy component is a WE43 magnesium alloy component prepared by the method described in claim 3, its electrical conductivity is 6.03 MS / m, its tensile strength in the horizontal direction in the deposited state is 240.1 MPa, its yield strength is 164 MPa, and its elongation is 11.5%; after the T6 heat treatment described in claim 4, its peak hardness is 93.2 HV, which is more than 17% higher than that in the deposited state.

10. The magnesium alloy component according to claim 7, characterized in that: The magnesium alloy component is an AZ31 / WE43 dissimilar magnesium alloy gradient functional integrated component prepared by the method described in claim 5 or 6. Performance zoning design is achieved through alternating CMT layer deposition: the WE43 side provides high-strength structural load-bearing capacity, and the AZ31 side provides high-conductivity broadband electromagnetic shielding capability. A 40–60 μm wide compositional transition band is formed between the AZ31 and WE43 layers, with Al and Zn elements diffusing towards the WE43 side, and Y, Gd, and Zr elements diffusing towards the AZ31 side, without harmful element segregation. The interface phase is α-Mg and trace amounts of Mg2Y phase. The hardness smoothly transitions from 80–86 HV on the WE43 side to 58–72 HV on the AZ31 side. The electrical conductivity of the fused component is 9.51 MS / m.